IMPLEMENTASI PEMBELAJARAN HADITS MELALUI METODE GERAKAN UNTUK MENINGKATKAN HAFALAN DAN KUALITAS SDM DI DESA WIBAMULYA - Adelin, Nur; Lubis, Rabiyannur; Irham, Irham (Universitas Islam 45 Bekasi, 2024)
Learning Hadith for children, let alone memorizing and applying it in everyday life, is very important and good for children's brain development. The rapid development of children's brain makes it easier for educators to develop aspects of their development, one of which is religious values, positive habits that children will use in their daily lives. Based on the analysis of the problems received by the author from the community in Wibawamulya Village, with the availability of the number of Qur'anic education parks with adequate infrastructure, it is still necessary to make efforts to increase the literacy of hadith education by implementing a program to improve the quality of human resources in Wibawamulya Village with hadith education using the motion method. Children lack concentration when learning hadith, feel bored and less interested in learning hadith so that memorization of hadith is not well achieved and forget the hadith that has been learned before. This causes the class to be noisy and not conducive when learning hadith takes place. Children prefer to talk to themselves when the educator is guiding their memorization. Based on the existing problems, the author uses qualitative research methods. The purpose of this community service is to understand hadith learning and can be implemented to students. The method of implementing this community service applies community education methods in the form of teaching and training. The results of the service have a positive impact in the form of increasing interest in learning hadith, memorizing hadith, and teacher creativity in learning methods.